(untitled) (Biological Sciences - PJSIR, 2022)
The anticoccidial drug’ toltrazuriJ’ was tested on the microsporidium Nosema bombycis in Helicoverpa zea, both by exposing larvae to drug after they had been infected with the microsporidia and by exposing uninfected larvae to the drug and microsporidian spores simultaneously. The drug at concentrations of 100, 200 and 400 ug/larva had no effect on the level of infection, estimated by the number of spores harvested from the larvae on day 8 post drug treatment. Midgut tissues from infected larvae, which had consumed 400flg of toltrazuril, still had massive infections of the parasite, and no cytological alterations of the parasite were observed when infected tissues were examined by light and electron microscopy. The pH of the gut of H. zea is alkaline and should not have affected the solubility of the drug nor its absorption into the midgut cells. It is concluded that toltrazuril, even at a dose of 400flg per larva, has no effect on N. bombycis in H. zea